Feynman diagram techniques in condensed matter physics - Jishi, Radi A., 1955- (2013)
"A concise introduction to Feynman diagram techniques, this book shows how they can be applied to the analysis of complex many-particle systems, and offers a review of the essential elements of quantum mechanics, solid state physics and statistical mechanics. Alongside a detailed account of the method of second quantization, the book covers topics such as Green's and correlation functions, diagrammatic techniques, superconductivity and contains several case studies. Some background knowledge in quantum mechanics, solid state physics and mathematical methods of physics is assumed. Detailed derivations of formulas and in-depth examples and chapter exercises from various areas of condensed matter physics make this a valuable resource for both researchers and advanced undergraduate students in condensed-matter theory, many-body physics and electrical engineering. Solutions to exercises are made available online"--
Machine generated contents note: Preface; 1. A brief review of quantum mechanics; 2. Single-particle states; 3. Second quantization; 4. The electron gas; 5. A brief review of statistical mechanics; 6. Real-time Green's and correlation functions; 7. Applications of real-time Green's functions; 8. Imaginary-time Green's and correlation functions; 9. Diagrammatic techniques; 10. Electron gas: a diagrammatic approach; 11. Phonons, photons, and electrons; 12. Superconductivity; 13. Nonequilibrium Green's function; Appendices; Index.
Includes bibliographical references and index.
Keywords: Feynman diagrams; Many-body problem; Condensed matter; SCIENCE / Physics